Recent advancements in urea biosensors for biomedical applications - Saravjeet Singh; Minakshi Sharma; Geeta Singh (IET Nanobiotechnology)
Abstract The quick progress in health care technology as a recurrent measurement of biochemical factors such as blood components leads to advance development and growth in biosensor technology necessary for effectual patient concern. The review wok of authors present a concise information and brief discussion on the development made in the progress of potentiometric, field effect transistor, graphene, electrochemical, optical, polymeric, nanoparticles and nanocomposites based urea biosensors in the past two decades. The work of authors is also centred on different procedures/methods for detection of urea by using amperometric, potentiometric, conductometric and optical processes, where graphene, polymer etc. are utilised as an immobilised material for the fabrication of biosensors. Further, a comparative revision has been accomplished on various procedures of urea analysis using different materials‐based biosensors, and it discloses that electrochemical and potentiometric biosensor is the most promise one among all, in terms of rapid response time, extensive shelf life and resourceful design.